Pasteurella multocida Pm0442 Affects Virulence Gene Expression and Targets TLR2 to Induce Inflammatory Responses - He, Fang; Qin, Xiaobin; Xu, Na; Li, Pan; Wu, Xiaoyan; Duan, Lijie; Du, Yiyang; Fang, Rendong; Hardwidge, Philip R.; Li, Nengzhang; Peng, Yuanyi (Frontiers in Microbiology, 2020)
Pasteurella multocida is an important pathogenic bacterium of domestic animals. However, the mechanisms of infection are still poorly understood. Here, we found that Pm0442 was dramatically up-regulated in infected mice among 67 predicted lipoproteins of P. multocida serotype A CQ2 strain (PmCQ2). To explore the role of Pm0442 in virulence and the potential of the mutant as a vaccine, Pm0442 mutant of PmCQ2 was successfully constructed. Then, the virulence characteristics, immune/inflammatory responses, and the survival rates of challenged mice were determined. As a result, it was found that the Pm0442 deletion of PmCQ2 significantly decreased bacterial loads and inflammatory responses of lung tissue in mice, resulting in improved survival. Mechanically, Pm0442 affects PmCQ2 capsular and lipopolysaccharide (LPS) synthesis and iron utilization-related genes expression affecting adhesion and phagocytosis. Furthermore, PM0442 bound directly to Toll-like receptor 2 (TLR2) to mediate the secretion of pro-inflammatory cytokine (IL-1β, TNF-α, IL-6, and IL-12p40) in macrophages via activation of the NF-κB, ERK1/2 and p38 signaling pathways. Notably, PmCQ2Δ0442 could provide 70–80% protection to mice challenged with 3.08 × 107 CFU of PmCQ2. Our findings demonstrate that Pm0442 is a virulence-related gene of PmCQ2, which provides new guidance for the prevention and control of Pasteurellosis.